Optimization-based reliability control of mechatronic systems - Meyer, Tobias
Reliability-adaptive systems allow an adaptation of system behavior based on current system reliability. They can extend their lifetime at the cost of lowered performance or vice versa. This can be used to adapt failure behavior according to a maintenance plan, thus increasing availability while using up system capability fully. To facilitate setup, a control algorithm independent of a degradation model is desired. A closed loop control technique for reliability based on a health index, a measure for system degradation, is introduced. It uses self-optimization as means to implement behavior adaptation. This is based on selecting the priorities of objectives that the system pursues. Possible working points are computed beforehand using model-based multiobjective optimization techniques. The controller selects the priorities of objectives and this way balances reliability and performance. As exemplary application, an automatically actuated single plate dry clutch is introduced. The entire reliability control is setup and lifetime experiments are conducted. Results show that the variance of time to failure is reduced greatly, making the failure behavior more predictable. At the same time, the desired usable lifetime can be extended at the cost of system performance to allow for changed maintenance intervals. Together, these possibilities allow for greater system usage and better planning of maintenance.
Keywords: dependability; reliability; behavior adaptation; self-optimization; multiobjective optimization; optimal control; automotive drivetrain; clutch system; reliability-adaptive system

Preceramic core-shell particles for the preparation of hybrid colloidal crystal films by melt-shear organization and conversion into porous ceramics - Vowinkel, Steffen; Boehm, Anna; Schäfer, Timmy; Gutmann, Torsten; Ionescu, Emanuel; Gallei, Markus (Materials & Design)
In this work, the preparation of porous hybrid particle-based films by core-shell particle design and convenient film preparation is reported. Monodisperse core particles consisting of poly(methyl methacrylate‑co‑allyl methacrylate) (P(MMA‑co‑ALMA)) were synthesized by starved-feed emulsion polymerization followed by the introduction of an initiator-containing monomer (inimer) for subsequent atom transfer radical polymerization (ATRP). The inimer shell allowed for the introduction of allylhydrido polycarbosilane (SMP-10) under ATRP conditions by grafting to the core particles. The functionalization of the prepared core-shell particles was investigated by IR spectroscopy (FTIR), scanning transmission electron microscopy (STEM) and solid-state NMR combined with dynamic nuclear polarization (DNP). The obtained hard core/soft preceramic shell particles were subjected to the melt-shear organization technique, enabling a convenient alignment into a colloidal crystal structure in one single step without the presence of a dispersion medium or solvent for the designed particles. Moreover, the hybrid particle-based films were converted into a porous ceramic structure upon thermal treatment. As a result, freestanding ceramic porous films have been obtained after degradation of the organic template core particles. Noteworthy, the conversion of the matrix material consisting of SMP-10 into the ceramic occurred with preservation of the pristine colloidal crystal template structure. Herein, the first example of core-shell particle preparation by combining different polymerization methodologies and application of the convenient melt-shear organization technique is shown, paving a new way to ceramic materials with tailored morphology and porosity.
Keywords: emulsion polymerization; self-assembly; ATRP; Colloidal crystal; Hybrid film; Particle processing

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Computational self-awareness as design approach for visual sensor nodes - Guettatfi, Zakarya; Hübner, Philipp; Platzner, Marco; Rinner, Bernhard (12th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC))
Keywords: embedded systems; image sensors; power aware computing; wireless sensor networks; Zynq-based VSN node prototype; computational self-awareness; design approach; platform levels; power consumption; visual sensor networks; visual sensor nodes; Cameras; Hardware; Middleware; Multicore processing; Operating systems; Runtime; Reconfigurable platforms; distributed embedded systems; performance-resource trade-off; self-awareness; visual sensor nodes

Self-Adjusting Monitor for Measuring Aging Rate and Advancement - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; Navabi, Zainalabedin (IEEE Transactions on Emerging Topics in Computing)
Time-variant age information of different parts of a system can be used for system-level performance improvement through high-level task scheduling, thus extending the life-time of the system. Progressive age information should provide the age state that the system is in, and the rate that it is being aged at. In this paper, we propose a structure that monitors certain paths of a circuit and detects its gradual age growth, and provides the aging rate and aging state of the circuit. The proposed monitors are placed on a selected set of nodes that represent a timing bottleneck of the system. These monitors sample expected data on these nodes, and compare them with the expected values. The timing of sampling changes as the circuit ages and its delay increases. The timing of sampling will provide a measure of aging advancement of a circuit. To assess the efficacy of the proposed method and compare it with other state-of-the-art aging monitors, we use them on selected nodes of the execution unit of different processors, as well as some circuits from ITC99 benchmarks. The results reveal that the precision of our proposed method is between 0.12 (ns) to 0.401 (ns). Its Area and power overhead are negligible and are about 2.13 and 0.69 percent respectively.
Keywords: Age advancement; age monitoring clock; aging rate; self-adjusting monitors

Free-Standing and Self-Crosslinkable Hybrid Films by Core-Shell Particle Design and Processing - Vowinkel, S.; Paul, S.; Gutmann, Torsten; Gallei, M. (Nanomaterials)
The utilization and preparation of functional hybrid films for optical sensing applications and membranes is of utmost importance. In this work, we report the convenient and scalable preparation of self-crosslinking particle-based films derived by directed self-assembly of alkoxysilane-based cross-linkers as part of a core-shell particle architecture. The synthesis of well-designed monodisperse core-shell particles by emulsion polymerization is the basic prerequisite for subsequent particle processing via the melt-shear organization technique. In more detail, the core particles consist of polystyrene (PS) or poly(methyl methacrylate) (PMMA), while the comparably soft particle shell consists of poly(ethyl acrylate) (PEA) and different alkoxysilane-based poly(methacrylate)s. For hybrid film formation and convenient self-cross-linking, different alkyl groups at the siloxane moieties were investigated in detail by solid-state Magic-Angle Spinning Nuclear Magnetic Resonance (MAS, NMR) spectroscopy revealing different crosslinking capabilities, which strongly influence the properties of the core or shell particle films with respect to transparency and iridescent reflection colors. Furthermore, solid-state NMR spectroscopy and investigation of the thermal properties by differential scanning calorimetry (DSC) measurements allow for insights into the cross-linking capabilities prior to and after synthesis, as well as after the thermally and pressure-induced processing steps. Subsequently, free-standing and self-crosslinked particle-based films featuring excellent particle order are obtained by application of the melt-shear organization technique, as shown by microscopy (TEM, SEM).
Keywords: Materials Science; Science & Technology - Other Topics; solid-state nmr; spectroscopy; catalysts; colloidal crystals; colloids; cross-linking; elastomeric opal films; emulsion polymerization; gamma-methacryloxypropyltrimethoxysilane; hybrid films; melt-shear organization; nanoparticles; particle; photons; polymers; processing; self-assembly; transition

Thermoreversible Self-Assembly of Perfluorinated Core-Coronas Cellulose-Nanoparticles in Dry State - Wang, Yonggui; Groszewicz, Pedro B.; Rosenfeldt, Sabine; Schmidt, Hendrik; Volkert, Cynthia A.; Vana, Philipp; Gutmann, Torsten; Buntkowsky, Gerd; Zhang, Kai (Advanced Materials)
Self-assembly of nanoparticles (NPs) forming unique structures has been investigated extensively over the past few years. However, many self-assembled structures by NPs are irreversible, because they are generally constructed using their suspensions. It is still challenging for NPs to reversibly self-assemble in dry state, let alone of polymeric NPs with general sizes of hundreds of nm. Herein, this study reports a new reversible self-assembly phenomenon of NPs in dry state, forming thermoreversible strip-like supermolecular structures. These novel NPs of around 150 nm are perfluorinated surface-undecenoated cellulose nanoparticles (FSU-CNPs) with a core-coronas structure. The thermoreversible self-assembled structure is formed after drying in the air at the interface between FSU-CNP films and Teflon substrates. Remarkably, the formation and dissociation of this assembled structure are accompanied by a reversible conversion of the surface hydrophobicity, film transparency, and anisotropic properties. These findings show novel feasibility of reversible self-assembly of NPs in dry state, and thereby expand our knowledge of self-assembly phenomenon.
Keywords: nanoparticles; self-assembly; cellulose; core-coronas structure; thermoreversible

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

Self-Aware and Self-Expressive Systems – Guest Editor's Introduction - Torresen, Jim; Plessl, Christian; Yao, Xin (IEEE Computer)
Keywords: self-awareness; self-expression

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Advantages of reliability-adaptive system operation for maintenance planning - Meyer, Tobias; Kaul, Thorben; Sextro, Walter (Proceedings of the 9th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes)
Intelligent mechatronic systems other the possibility to adapt system behavior to current dependability. This can be used to assure reliability by controlling system behavior to reach a pre-defined lifetime. By using such closed loop control, the margin of error of useful lifetime of an individual system is lowered. It is also possible to change the pre-defined lifetime during operation, by adapting system behavior to derate component usage. When planning maintenance actions, the remaining useful lifetime of each individual system has to be taken into account. Usually, stochastic properties of a fleet of systems are analyzed to create maintenance plans. Among these, the main factor is the probability of an individual system to last until maintenance. If condition-based maintenance is used, this is updated for each individual system using available information about its current state. By lowering the margin of error of useful lifetime, which directly corresponds to the time until maintenance, extended maintenance periods are made possible. Also using reliability-adaptive operation, a reversal of degradation driven maintenance planning is possible where a maintenance plan is setup not only according to system properties, but mainly to requirements imposed by maintenance personnel or infrastructure. Each system then adapts its behavior accordingly and fails according to the maintenance plan, making better use of maintenance personnel and system capabilities at the same time. In this contribution, the potential of maintenance plan driven system behavior adaptation is shown. A model including adaptation process and maintenance actions is simulated over full system lifetime to assess the advantages gained.
Keywords: Adaptive systems; Reliability analysis; Availability; Adaptive control; Maintenance; Self-optimizing systems; Self-optimizing control; Stochastic Petri-nets

On Optimal Smoothing in Minimum Statistics Based Noise Tracking - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Interspeech 2015)
Noise tracking is an important component of speech enhancement algorithms. Of the many noise trackers proposed, Minimum Statistics (MS) is a particularly popular one due to its simple parameterization and at the same time excellent performance. In this paper we propose to further reduce the number of MS parameters by giving an alternative derivation of an optimal smoothing constant. At the same time the noise tracking performance is improved as is demonstrated by experiments employing speech degraded by various noise types and at different SNR values.
Keywords: speech enhancement; noise tracking; optimal smoothing

Hierarchisches Optimierungskonzept für die Laststeuerung von Haushaltsgeräten - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (ETG-Fachtagung "Von Smart Grids zu Smart Markets")
Haushaltsgeräte aus der Klasse der "Weißen Ware" tragen mit etwa einem Drittel ($34,2%$ \citeBDEW2013) zum privaten Energieverbrauch bei. Diese Veröffentlichung präsentiert eine Struktur und die dafür notwendige optimale Betriebsstrategie für Weiße Ware in einer Umgebung mit Strompreisen, die wegen der Volatilität der Regenerativen Energien stark fluktuieren. Das vorgeschlagene Konzept nutzt dafür ein dezentrales Energiemanagementsystem, das über drei Hierarchieebenen verteilt ist: die Geräteebene, die Haushaltsebene und die Ortsnetzebene. Auf der Geräteebene nutzt dieses Konzept zusätzlich Betriebsflexibilitäten der Haushaltsgeräte aus.
Keywords: Energy management; hybrid energy storage system; self-optimization; multi-objective optimization; adaptive systems; pareto set; SFB614-D1; SFB614-D2; LEA-Publikation; Eigene

Request Driven Social Sensing - King, Thomas C.; Liu, Qingzhi; Polevoy, Gleb; de Weerdt, Mathijs; Dignum, Virginia; van Riemsdijk, M. Birna; Warnier, Martijn (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: crowd-sensing; crowdsourcing; data aggregation; game theory; norms; reciprocation; self interested agents; simulation

PEM fuel cell prognostics using particle filter with model parameter adaptation - Kimotho, James Kuria; Meyer, Tobias; Sextro, Walter (Prognostics and Health Management (PHM), 2014 IEEE Conference on)
Application of prognostics and health management (PHM) in the field of Proton Exchange Membrane (PEM) fuel cells is emerging as an important tool in increasing the reliability and availability of these systems. Though a lot of work is currently being conducted to develop PHM systems for fuel cells, various challenges have been encountered including the self-healing effect after characterization as well as accelerated degradation due to dynamic loading, all which make RUL predictions a difficult task. In this study, a prognostic approach based on adaptive particle filter algorithm is proposed. The novelty of the proposed method lies in the introduction of a self-healing factor after each characterization and the adaption of the degradation model parameters to fit to the changing degradation trend. An ensemble of five different state models based on weighted mean is then developed. The results show that the method is effective in estimating the remaining useful life of PEM fuel cells, with majority of the predictions falling within 5% error. The method was employed in the IEEE 2014 PHM Data Challenge and led to our team emerging the winner of the RUL category of the challenge.
Keywords: ageing; particle filtering (numerical methods); proton exchange membrane fuel cells; remaining life assessment; PEM fuel cell prognostics; PHM; RUL predictions; accelerated degradation; adaptive particle filter algorithm; dynamic loading; model parameter adaptation; prognostics and health management; proton exchange membrane fuel cells; remaining useful life estimation; self-healing effect; Adaptation models; Data models; Degradation; Estimation; Fuel cells; Mathematical model; Prognostics and health management

Closed-loop Control System for the Reliability of Intelligent Mechatronic Systems - Meyer , Tobias; Sextro, Walter (Proceedings of the Second European Conference of the Prognostics and Health Management Society 2014)
So-called reliability adaptive systems are able to adapt their system behavior based on the current reliability of the system. This allows them to react to changed operating conditions or faults within the system that change the degradation behavior. To implement such reliability adaptation, self-optimization can be used. A self-optimizing system pursues objectives, of which the priorities can be changed at runtime, in turn changing the system behavior. When including system reliability as an objective of the system, it becomes possible to change the system based on the current reliability as well. This capability can be used to control the reliability of the system throughout its operation period in order to achieve a pre-defined or user-selectable system lifetime. This way, optimal planning of maintenance intervals is possible while also using the system capabilities to their full extent. Our proposed control system makes it possible to react to changed degradation behavior by selecting objectives of the self-optimizing system and in turn changing the operating parameters in a closed loop. A two-stage controller is designed which is used to select the currently required priorities of the objectives in order to fulfill the desired usable lifetime. Investigations using a model of an automotive clutch system serve to demonstrate the feasibility of our controller. It is shown that the desired lifetime can be achieved reliably.
Keywords: self-optimization reliability adaptive

Method to Identify Dependability Objectives in Multiobjective Optimization Problem - Meyer , Tobias; Sondermann-Wölke, Christoph; Sextro, Walter (Conference Proceedings of the 2nd International Conference on System-Integrated Intelligence)
Intelligent mechatronic systems, such as self-optimizing systems, allow an adaptation of the system behavior at runtime based on the current situation. To do so, they generally select among several pre-defined working points. A common method to determine working points for a mechatronic system is to use model-based multiobjective optimization. It allows finding compromises among conflicting objectives, called objective functions, by adapting parameters. To evaluate the system behavior for different parameter sets, a model of the system behavior is included in the objective functions and is evaluated during each function call. Intelligent mechatronic systems also have the ability to adapt their behavior based on their current reliability, thus increasing their availability, or on changed safety requirements; all of which are summed up by the common term dependability. To allow this adaptation, dependability can be considered in multiobjective optimization by including dependability-related objective functions. However, whereas performance-related objective functions are easily found, formulation of dependability-related objective functions is highly system-specific and not intuitive, making it complex and error-prone. Since each mechatronic system is different, individual failure modes have to be taken into account, which need to be found using common methods such as Failure-Modes and Effects Analysis or Fault Tree Analysis. Using component degradation models, which again are specific to the system at hand, the main loading factors can be determined. By including these in the model of the system behavior, the relation between working point and dependability can be formulated as an objective function. In our work, this approach is presented in more detail. It is exemplified using an actively actuated single plate dry clutch system. Results show that this approach is suitable for formulating dependability-related objective functions and that these can be used to extend system lifetime by adapting system behavior.
Keywords: Self-optimization; multiobjective optimization; objective function; dependability; intelligent system; behavior adaptation